Knowledge and Behavior regarding Consumption of Herbal Galactagogues among Breastfeeding Women in Mataram City - I Gusti Agung Ayu Hari Triandini; Ni Made Gita Gumangsari; I Gde Adi Suryawan Wangiyana (EMBRIO: Jurnal Kebidanan, 2023)
Mataram city occupied the region with the lowest coverage of exclusive breastfeeding in West Nusa Tenggara in 2022. One of the causes of the failure of exclusive breastfeeding is the lack of breast milk production. Galactagogues are substances that can increase breast milk production. A relatively safe alternative to support breast milk production is to consume herbs containing galactagogues. It is essential to trace local culture, knowledge, and behavior regarding herbal galactagogues to get insight into the types of galactagogues, their properties as well as side effects. Scientific studies are required to be used as a reference for breastfeeding women. This study aims to describe knowledge and behavior of breastfeeding women regarding the consumption of galactagogues. The study applied mixed-method design with a cross-sectional approach to conduct a survey on knowledge and behavior regarding consumption of herbal galactagogues. Data were collected by distributing questionnaires to respondents who were selected based on inclusion criteria, namely breastfeeding women with children aged 0 to 6 months, domiciled in the city of Mataram and registered at the Community Health Center in the city of Mataram, as many as 124 people. It was found that most of respondent had a poor level of knowledge by 62.1 percent, while 37.1percent of them had good consumption behavior of herbal galactagogues. It can be concluded that generally, the people of Mataram City consumed herbal galactagogues more often based on empirical evidence from generation to generation. Thus, additional information regarding variations of other herbal galactagogues is required to support exclusive breastfeeding coverage.